Analysis of Local Government Readiness for Implementing AI Based Human Resource Information Systems - Josse Aprilio Mangontan; Moh. Afrisyal L. Madusu; Putri Desi Ananta; La Saudin (www.amertainstitute.com, 2025)
This study aims to analyze the readiness of local governments in adopting Artificial Intelligence (AI) based Human Resource Information Systems (HRIS) as a strategy to improve public sector efficiency and responsiveness in the digital era. The research adopts a quantitative approach using a survey method with structured questionnaires distributed to selected government agencies. The dimensions of organizational readiness measured include infrastructure readiness, human resource capability, policy support, and digital literacy. Data were collected from 112 respondents consisting of HR officers and IT staff in local government institutions. The analysis was conducted using descriptive statistics and structural equation modeling (SEM) to assess relationships between variables.The results show that while technological infrastructure and policy support are relatively adequate, there are still significant challenges in terms of human resource competency and digital adaptation. Particularly, the lack of training in AI application and limited integration between departments hinder effective implementation. The readiness level was categorized as moderate, indicating the need for targeted improvements before full scale deployment. The significance of this study lies in its contribution to the discourse on public sector digital transformation, especially in the context of human resource management through AI. The findings provide practical insights for policymakers and government leaders to design tailored interventions that address gaps in readiness. It also highlights the strategic importance of aligning institutional vision, technical capabilities, and workforce development to support AI based system implementation. This research is expected to serve as a foundation for further academic exploration and a reference for strategic planning in public administration.